Studying the effect of grain size on the concentration of lead and cadmium of modern marine sediments dispersed along the beach of Tartous city. - سامر غدير غدير; حسام الدين كريم لايقه (Latakia University Journal -Basic Sciences Series, 2022)
Grain size, sorting, skewness, and kurtosis studies are of great importance in order to texturally characterize the sedimentary environments. These parameters are useful in characterizing the dynamic beach environment, which is of potential interest for research in natural resources and in the interpretation of marine sediment pollution. The purpose of this research is to investigate the concentrations of cadmium (Cd) and lead (Pb) in the modern marine sediments of the beach of Tartous city and link them with the granular composition of the sediments on the one hand and with the amount of organic matter on the other hand. Samples were taken from six different locations on the beach of Tartous city. The results of this study showed almost complete control of sand with the presence of some gravel sand, which in turn indicates high energy conditions. An important correlation was observed between the change in the concentrations of the studied mineral elements (Cd and Pb) and the quality of sediments and the amount of organic matter on the one hand, and with the difference in the quality and sources of pollution on the other hand. The concentrations of cadmium values ​​ranged (71.3 - 9.7 mg/kg), and lead 38.5 - 5.25 mg/kg) consistent with a rise in the percentage values ​​of the organic matter (3.87 - 15.17%) respectively, where the concentrations of the studied elements increased in the fine sedimentary samples due to the increase of the qualitative surface in the sites (St2, St3, &St4 St5) affected by sewage water compared to the rest of the sites ((St1: near the new port of Arwad) (St6: Porto Tartous tourist facility)) with fine sandy and coarse sandy sediments with the presence some gravel.